Evaluasi Penggunaan Obat Antituberkulosis di Instalasi Rawat Jalan Rumah Sakit X Kota Bontang - Jannah, Raodhatul; Rusli, Rolan; Maulida, Faizatun (Akademi Farmasi Bumi Siliwangi, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. TB treatment is carried out for a minimum of 6 months, namely the intensive phase of 2 months and the advanced phase of 4 months. Antituberculosis Drugs (ATD) consist of 4 types of drugs including Isoniazid (H), Rifampicin (R), Pyrazinamide (Z), and Ethambutol (E). Evaluation of drug use is carried out to ensure that the drug has been used appropriately, safely and effectively.This research is a descriptive observational study using retrospective patient medical record data. This study aims to determine the rationality of tuberculosis treatment in tuberculosis patients at the outpatient installation of Hospital X in Bontang city period January 2021 - June 2023. The most patient characteristics obtained from 88 patients were aged 56-65 years (26%), body weight 38-54 kg (45%), male gender (56%), working patients (52%), living in West Bontang District (27%), and having comorbidities (58%). The most use of OAT was given Fixed Dose Combination (FDC)-Intermittent Dose (84%). The rationality of using antituberculosis drugs based on the right category of indications is 100%, right drug is 98%, right dose is 97%, and right duration of drug administration is 95%.